The attitude of employers of creative leadership of the local public health institution of Oumza tebessa - Boussaha, Abla (Journal of Human Sciences, 2021)
This study aimed to unveil the attitude of employees of the local public health institution of Ouenza Tebessa towards the application of creative leadership, and to achieve the targets of this study, a sample made up of 40 employees from the local public health institution of Ouenza were selected by means of stratified sampling, the descriptive method was used based on the questionnaire as a means of data collection, to the Liker t scale .The results of the study showed that public employees have negative attitudes towards the leader’s application of originality, motivation and that they have positive attitudes towards the leader application of creative communication .The study also showed that there are statistically significant differences between the attitudes of employees of the local public health institution of Ouenza.